Planning of Oil and Gas Fields at PT JFS Using the AHP-Topsis Method as a Candidate for the Application of CCUS Technology Based on CO2 Injection EOR - Jonathan Fritz Simamora; Ruri Agung Wahyuono (International Journal Labs, 2026)
PT JFS’s mature oil and gas fields have experienced declining reservoir pressure, increasing water cut, and reduced productivity due to long-term reservoir depletion. To support efforts to enhance oil production while reducing carbon emissions, the integration of Carbon Capture, Utilization, and Storage (CCUS) with CO?-based Enhanced Oil Recovery (CO?-EOR) presents a significant implementation opportunity. This research aimed to determine the most potential field priorities for CO?-EOR implementation at PT JFS using a Multi-Criteria Decision-Making (MCDM) approach. Five alternative fields—Prabu, Lima, Ades, Pendekar, and Rambo—were evaluated based on five criteria and thirteen subcriteria identified through Focus Group Discussions with Subject Matter Experts (SMEs). The Analytical Hierarchy Process (AHP) was applied to determine the criteria weights, while the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was used to rank alternatives based on their proximity to the ideal solution. The results showed that Reservoir Properties had the highest weight (0.438), while Production Realization (0.215) and Permeability (0.183) were the most influential factors at the subcriterion level. Based on the TOPSIS analysis, the Ades field was selected as the highest-priority candidate, with a preference value of 0.865, followed by Prabu, Lima, and Pendekar, while Rambo ranked as the lowest-priority alternative. The developed AHP-TOPSIS model was validated using a case study at PT ABC, in which the Sukowan field was identified as the most feasible candidate compared with other alternatives, demonstrating the model’s consistency with actual technical and operational considerations. This model can serve as an objective, systematic, and consistent decision-support tool for CCUS project planning and has the potential for application in other oil and gas fields with similar characteristics.